The effect of mulching Mucuna breactata on the growth and yield performance of aerobic paddy / Wan Aulia Farzian Che Wan Abdullah Suffian - Che Wan Abdullah Suffian, Wan Aulia Farzian (Faculty of Plantation and Agrotechnology, 2019)
This research was conducted to investigate the effect of mulching Mucuna braectata on the growth and yield performance of aerobic paddy at Universiti Teknologi MARA (UiTM), Jasin Campus Melaka. There are several factors that can influence the growth and yield of the paddy plant such as water, nutrient and etc. The objectives of this studied was to determine the effect of using mulching Mucuna breactata on aerobic paddy growth performance and also to identify the effect of Mucuna breactata on yield performance of aerobic paddy. This experiment was carried out in Complete Randomized Design (CRD). There are two treatments with five replications that had been used in this experiment. The treatment consisted of mulching Mucuna breactata and also no mulching (control) and each of the treatment consist of five replications. Each aerobic paddy plant was planted in a pot and each pot were applied with 20 g of mulching act as treatments. Aerobic paddy variety (Aeron 1) was choosing in this experiment because of the rapid plant growth and this experiment was conducted for 90 days. The result showed that the paddy that applied with mulching had better growth performance for all parameter included plant height, number of tiller and plant biomass. It also showed that the treatment mulching is more effective to improve the plant growth than the treatment non- mulching (control). Lastly, the application of mulching on paddy plant can give many advantages because it showed that it had significantly affect the plant growth compared to non-mulching application. The yield of the aerobic paddy plant that applied mulching was low than the non-mulching(control) treatment. It was due to several factors that influence the yield of the paddy during experiment such as pest, disease and environment surrounding paddy.